Enhanced Photocatalytic Activity of TiO2 Powders (P25) via Calcination Treatment. (19th February 2012) - Wang, Guohong; Xu, Lin; Zhang, Jun; Yin, Tingting; Han, Deyan
Abstract : P25 TiO2 powders were calcined at different temperatures in a muffle furnace in air. The P25 powders before and after calcination treatment were characterized with XRD FTIR, UV-visible diffuse reflectance spectra, SEM, TEM, HRTEM, and N2 adsorption-desorption measurements. The photocatalytic activity was evaluated by the photocatalytic oxidation of methyl orange aqueous solution under UV light irradiation in air. The results showed that calcination treatment obviously influenced the microstructures and photocatalytic activity of the P25 TiO2 powders. The synergistic effect of the phase structure, BET surface area, and crystallinity on the photocatalytic of TiO2 powders (P25) after calcination was investigated. An optimal calcination temperature (500 ∘ C ) was determined. The photocatalytic activity of TiO2 powders calcined at 500 ∘ C was nearly 2 times higher than that of the uncalcined P25 TiO2 . The highest photocatalytic activities of the calcined samples at 500 ∘ C for 4 h might be ascribed to the enhancement of anatase crystallization and the optimal mass ratio (ca. 1 : 2) of rutile to anatase.